Rapid identification of a Mycobacterium tuberculosis full genetic drug resistance profile through whole genome sequencing directly from sputum. (September 2017) - Nimmo, Camus; Doyle, Ronan; Burgess, Carrie; Williams, Rachel; Gorton, Rebecca; McHugh, Timothy D.; Brown, Mike; Morris-Jones, Stephen; Booth, Helen; Breuer, Judith
Highlights: The detection of second-line drug resistance by rapid molecular tests is limited. Whole genome sequencing can provide a complete genetic drug resistance profile. Sequencing directly from sputum is faster than from culture isolates. In this case, WGS directly from sputum identified drug resistance and altered clinical management. This has the potential for expanded use where second-line resistance is common. Abstract: Introduction: Resistance to second-line tuberculosis drugs is common, but slow to diagnose with phenotypic drug sensitivity testing. Rapid molecular tests speed up diagnosis, but can only detect limited mutations. Whole genome sequencing (WGS) of culture isolates can generate a complete genetic drug resistance profile, but is delayed by the initial culture step. In the case presented here, successful WGS directly from sputum was achieved using targeted enrichment. Case report: A 29-year-old Nigerian woman was diagnosed with tuberculosis. Xpert MTB/RIF and Hain line probe assays identified rpoB and inhA mutations consistent with rifampicin and intermediate isoniazid resistance, and a further possible mutation conferring fluoroquinolone resistance. WGS directly from sputum identified a further inhA mutation consistent with high-level isoniazid resistance and confirmed the absence of fluoroquinolone resistance. Isoniazid was stopped, and the patient has completed 18 months of a fluoroquinolone-based regimen without relapse. Discussion: Compared to rapid molecular tests (which can only examine a limited number of mutations) and WGS of culture isolates (which requires a culture step), WGS directly from sputum can quickly generate a complete genetic drug resistance profile. In this case, WGS altered the clinical management of drug-resistant tuberculosis and demonstrated potential for guiding individualized drug treatment where second-line drug resistance is common.